Study on the Clinical Features of Parkinson's Disease With Probable Rapid Eye Movement Sleep Behavior Disorder - Kexin Long; Changmin Wan; Yaqin Xiang; Jiabin Liu; Qian Xu; Qiying Sun; Zhiqin Wang; Yun Tian; Liangjuan Fang; Yang Yang; Xinxiang Yan; Beisha Tang; et al. (Frontiers in Neurology, 2020)
Objective: To investigate the clinical features and factors associated with Parkinson's disease (PD) patients with probable rapid eye movement sleep behavior disorder (PD-pRBD).Methods: A total of 2,440 patients with clinically established or clinically probable PD were divided into two groups: PD-pRBD and PD without pRBD (PD-NRBD), according to the RBD questionnaire—Hong Kong. Data collection included demographic data, basic clinical history, and motor and non-motor symptoms. Based on the onset time of pRBD and the motor symptoms in PD, PD-pRBD patients were further divided into the pRBD prior to PD (PD-prRBD) group and the pRBD posterior to PD (PD-poRBD) group. Clinical features were compared between the PD-pRBD and PD-NRBD groups, as well as the PD-prRBD and PD-poRBD groups. The associated factors of pRBD were also explored.Results: The prevalence of pRBD was 41.4% (1,010 out of the total of 2,440) in our PD cohort. Further, compared with the PD-NRBD group, the PD-pRBD group had longer disease duration and more severe motor symptoms. Moreover, the PD-pRBD group had significantly higher levodopa equivalent daily dose and a higher ratio of dyskinesia, wearing-off, and offset of the Hoehn–Yahr stage. The scores on the non-motor symptom rating scale (NMSS), cognitive impairment, Parkinson's disease sleep scale (PDSS), excessive daytime sleepiness, constipation, hyposmia, depression, and the 39-item Parkinson's disease questionnaire also appeared worse in the PD-pRBD group. Significant differences in the educational level, disease duration, disease progression, Unified Parkinson's Disease Rating Scale (UPDRS)-II, UPDRS-III, tremor, rigidity, bradykinesia, posture gait, frozen gait, levodopa equivalent daily dose, dyskinesia, wearing-off, Hoehn–Yahr stage, NMSS-6, PDSS, and communication score widely existed between the PD-prRBD and PD-poRBD groups. Late-onset PD, long disease duration, high UPDRS-I score, high NMSS-4 score, low PDSS score, constipation, and hyposmia were all identified as the risk factors for PD-pRBD.Conclusions: Compared with the PD-NRBD group, the PD-pRBD group may have more severe motor symptoms, motor complications, and non-motor symptoms as well as a substandard quality of life. Further, late-onset PD, long disease duration, high UPDRS-I score, high NMSS-4 score, low PDSS score, constipation, and hyposmia can be risk factors for RBD in PD. Differences also occurred between the PD-prRBD and PD-poRBD groups.